2014
DOI: 10.1007/s10750-014-1976-4
|View full text |Cite
|
Sign up to set email alerts
|

European native Myriophyllum spicatum showed a higher $${\text{HCO}}_{3}^{ - }$$ HCO 3 - use capacity than alien invasive Myriophyllum heterophyllum

Abstract: Light, temperature, and the availability of carbon are three major drivers of submerged plant growth, photosynthesis, and competitive strength. A laboratory study using a three factorial experimental design (light 9 temperature 9 CO 2 ) was carried out to evaluate growth responses (RGR (relative growth rate), LDMC (leaf dry matter content), and root:shoot ratio) and physiological changes (pigment characteristics and net photosynthesis under CO 2 depletion) in the European native Myriophyllum spicatum and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Similarly, Thum & Lennon (2010) reported M. heterophyllum from ʺhigher orderʺ lakes characterized as large, low elevation systems with relatively high pH, alkalinity and conductivity. The optimum temperature for M. heterophyllum is about 20°C (Hussner & Jahns, 2015). According to Starmühler (2009), the taxon was found in a 3-10 m deep lake on the island of Krk, northern Adriatic.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Thum & Lennon (2010) reported M. heterophyllum from ʺhigher orderʺ lakes characterized as large, low elevation systems with relatively high pH, alkalinity and conductivity. The optimum temperature for M. heterophyllum is about 20°C (Hussner & Jahns, 2015). According to Starmühler (2009), the taxon was found in a 3-10 m deep lake on the island of Krk, northern Adriatic.…”
Section: Resultsmentioning
confidence: 99%
“…The affinity ratio for HCO 3 − relative to CO 2 during photosynthesis was highly variable among the 10 tested species (0.11–0.61), and it was suppressed for all species (to 0–0.28) by acclimation to elevated CO 2 . This phenomenon has been shown before for a few freshwater plants and marine macroalgae (Sand‐Jensen & Gordon, , ; Hussner & Jahns, ), but it is confirmed here for the first time as a general phenomenon for many species acclimated to specific air‐saturated and supersaturated CO 2 concentrations. It can be regarded as a suitable cost–benefit response because investment in costly HCO 3 − use mechanisms is futile, when free CO 2 is readily available.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 addition was adjusted for each pot with the needle regulator. The pH in the LC treatment was held constant at 8.2 ± 0.2, while pH in the HC treatment was fixed at 6.7 ± 0.2, resulting in CO 2 concentrations of 0.012 m m in the LC and 0.263 m m in the HC treatment (Hussner & Jahns, ). Due to the continuous addition of CO 2 in the HC treatment, DIC reached 0.8–0.95 m m , close to the 0.85 m m of the ambient air bubbled LC treatments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that this species is very resistant to submergence and that this feature may be one of the reasons for its success in habitats heavily disturbed by floods. Another experiment, carried out by Hussner & Jahns (2015) in Germany, evaluated the effects of light, temperature, and carbon availability on the invasive species Myriophyllum heterophyllum, and compared it with the European native M. spicatum. They showed that the native species attains better use of bicarbonate and has higher growth rates than the invasive species under low CO 2 availability.…”
Section: Invasibilitymentioning
confidence: 99%